The production of polyurethane from waste vegetable oil-based polyols and modelling of rheological properties - Aydoğmuş, Ercan; Kamişli, Fethi (International University of Sarajevo, 2017)
Polyols in polyurethane production is of great importance. The future will increase the production of polyols from renewable sources. The result of the reduction of fossil fuels will be important in the use of renewable resources. Especially important alternative which will expand polyols production from vegetable oils. Polyols derived from vegetable oil will be produced by epoxidation, hydroxylation and purification. In this study, some vegetable-oil based polyols were produced from the different wastes vegetables oils with the catalysts. The produced polyols compared with commercial polyols with rheological properties as viscosity, temperature, shear stress, shear rate. The rheological properties of the polyols were modelling with general equations based on experimental data. Polyurethane produced from waste vegetable oil-based polyols and investigated density and effective thermal conductivity.
Keywords: Modelling; Polyurethane; Rheological properties; Waste vegetable oil-based polyols